Demystifying Artificial Intelligence in Medicine - Solar Cafaggi, Sofia (University of Ottawa Journal of Medicine, 2020)
The Artificial Intelligence (AI) revolution is disrupting a variety of industries – from manufacturing to agriculture, intellectual property, or retail. Healthcare, a complex industry with countless areas for improvement, will be no different. The effect of AI in medicine and delivery of care is already a source of both excitement and concern. The excitement brings about hope for better treatments and improved delivery thereof; but it also brings uncertainty as to what the future of a physician will be in an AI-reliant world, and the ethical and legal implications this technology will bring about.